Implementasi Model Jigsaw Pada Pembelajaran Sistem Kelistrikan Kapal - Egbert Edward Djajasasana; Nenny; Rusli Achmad (Politeknik Pelayaran Barombong, 2021)
Abstract. This study aims to determine the implementation of the Jigsaw cooperative learning model on the learning outcomes of the ship's electrical system in the second semester of the Barombong Shipping Polytechnic. The jigsaw cooperative learning model is a model of student learning in small groups of 5-6 people with heterogeneous groups, cooperating positively and each member is responsible for learning a particular problem from the material provided and conveying the material to other group members. This research is a Classroom Action Research consisting of two cycles with the stages of planning, implementation, observation and reflection. The data analysis technique used is descriptive qualitative analysis technique. The subjects of this study were 16 people in class 2 B majoring in ship engineering. Data collection techniques using tests, observation, documentation, questionnaires and field notes. The results showed that based on the learning outcomes obtained in the first cycle it can be seen that the total average score of 75.62 and 75% classical completeness and the second cycle the average score of 82 and 73% classical completeness. The implementation of the jigsaw cooperative learning model can improve learning outcomes because it provides opportunities for students to think critically on a problem and find a concept directly from the results of the analysis.